Physical characterization of functionalized spider silk: electronic and sensing properties - Eden Steven, Jin Gyu Park, Anant Paravastu, Elsa Branco Lopes, James S Brooks, Ongi Englander, Theo Siegrist, Papatya Kaner and Rufina G Alamo (Science and Technology of Advanced Materials, 2011)
This work explores functional, fundamental and applied aspects of naturally harvested spider silk fibers. Natural silk is a protein polymer where different amino acids control the physical properties of fibroin bundles, producing, for example, combinations of β-sheet (crystalline) and amorphous (helical) structural regions. This complexity presents opportunities for functional modification to obtain new types of material properties. Electrical conductivity is the starting point of this investigation, where the insulating nature of neat silk under ambient conditions is described first. Modification of the conductivity by humidity, exposure to polar solvents, iodine doping, pyrolization and deposition of a thin metallic film are explored next. The conductivity increases exponentially with relative humidity and/or solvent, whereas only an incremental increase occurs after iodine doping. In contrast, iodine doping, optimal at 70 °C, has a strong effect on the morphology of silk bundles (increasing their size), on the process of pyrolization (suppressing mass loss rates) and on the resulting carbonized fiber structure (that becomes more robust against bending and strain). The effects of iodine doping and other functional parameters (vacuum and thin film coating) motivated an investigation with magic angle spinning nuclear magnetic resonance (MAS-NMR) to monitor doping-induced changes in the amino acid-protein backbone signature. MAS-NMR revealed a moderate effect of iodine on the helical and β-sheet structures, and a lesser effect of gold sputtering. The effects of iodine doping were further probed by Fourier transform infrared (FTIR) spectroscopy, revealing a partial transformation of β-sheet-to-amorphous constituency. A model is proposed, based on the findings from the MAS-NMR and FTIR, which involves iodine-induced changes in the silk fibroin bundle environment that can account for the altered physical properties. Finally, proof-of-concept applications of functionalized spider silk are presented for thermoelectric (Seebeck) effects and incandescence in iodine-doped pyrolized silk fibers, and metallic conductivity and flexibility of micron-sized gold-sputtered silk fibers. In the latter case, we demonstrate the application of gold-sputtered neat spider silk to make four-terminal, flexible, ohmic contacts to organic superconductor samples.